ANALISIS PENGARUH KEMAMPUAN KERJA, MOTIVASI KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - Umi Lestari, 0635020702 (Students Journal of Economic and Management, 2013)
Development of insurance industry in Indonesia increasingly moving rapidly. It is characterized by the increasing number of insurance companies that stand, which means the level of competition is gettingsharper peers. Success is not obtained because of the support of human resources (employees) who qualified for a major asset in helping the company achieve its goals. This research was conducted at PT Prudential Life Assurance Yogyakarta by using all census population sampled as many as 63 people and decent questionnaires processed sebantak 63 questionnaire. Results of regression testing obtained results Adjusted R Square of 0.836 means that the change of variables can be explained by the variable performance of work ability, work motivation and job satisfaction was 83.6%. As for the F test showed that the ability to work together, work motivation and job satisfaction affect the performance. Based on the partial regression testing signifinasi kemapuan known work on performance is 0.047 <0.05, significance of work motivation on performance is 0.000 <0.05, significance of job satisfaction on performance is 0.000. < 0.05. It is identified that all the hypotheses accepted or proven.